1998
DOI: 10.1007/pl00007449
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic mechanisms in corneal ulceration and repair

Abstract: Corneal stromal ulceration is a devastating disorder that can cause blindness. Stromal ulceration was once thought to be a physical dissolution process, which even now is described as "melting." However, a major paradigm change occurred about 25 years ago with the demonstration of extracellular matrix-degrading activity associated with tissues isolated from ulcerating corneas. Recent studies have identified the enzymes involved as specific members of the matrix metalloproteinase (MMP) family. These studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 30 publications
2
110
0
6
Order By: Relevance
“…44,46 Gelatinase B has been detected in the corneal basal epithelial cells at the edges of non-healing corneal ulcers in humans. This suggests 31 Garrana et al reported that the expression of metalloproteinase-2 was upregulated in corneas with recurrent erosions. These findings suggest that MMPs may be responsible for the breakdown of the anchoring molecules in the basement membrane during epithelial healing, and this is the basis for the use of inhibitors of MMP in the treatment of RCE.…”
Section: Inhibitors Of Mmpmentioning
confidence: 93%
See 2 more Smart Citations
“…44,46 Gelatinase B has been detected in the corneal basal epithelial cells at the edges of non-healing corneal ulcers in humans. This suggests 31 Garrana et al reported that the expression of metalloproteinase-2 was upregulated in corneas with recurrent erosions. These findings suggest that MMPs may be responsible for the breakdown of the anchoring molecules in the basement membrane during epithelial healing, and this is the basis for the use of inhibitors of MMP in the treatment of RCE.…”
Section: Inhibitors Of Mmpmentioning
confidence: 93%
“…The matrices undergo constant, slow remodelling during health and rapid remodelling during repair. [28][29][30][31][32] Corneal stromal remodelling during wound healing is mediated by a group of zinc containing degradative enzymes known as matrix metalloproteinases (MMPs). 33,34 They appear in a precisely controlled sequence that suggest they perform specific roles.…”
Section: Role Of Mmp Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…MMPs play major physiological roles in degrading and remodeling the ECM. The presence of a clone encoding gelatinase-B (B66) is significant, because MMP-9 has been shown to be expressed in wounded corneal epithelium and is implicated in corneal ulceration and graft rejection (Berman, 1989;Fini et al, 1995Fini et al, , 1996Fini et al, , 1998Barro et al, 1998;Ye and Azar, 1998;Carinato et al, 2000). MMPs have also been implicated in regeneration (Yang and Bryant, 1994;Yang et al, 1997).…”
Section: A Profile Of Gene Expression In Transdifferentiating Cornea mentioning
confidence: 99%
“…Under physiologic conditions, MMPs activity is tightly controlled, and primary models of regulation include transcriptional control, zymogen activation and dynamic inhibition by tissue inhibitors of metalloproteinases [20]. The metastatic and invasive potential of many cancers also depends on the expression of MMPs and MMP-2 over expression and activity associated with the invasive potential of human tumours [21].…”
Section: Discussionmentioning
confidence: 99%